Comparing the performance of body mass index, waist circumference and waist-to-height ratio in predicting Malaysians with excess adiposity. (17th November 2022) - Low, Nie Yen; Chan, Chin Yi; Subramaniam, Shaanthana; Chin, Kok-Yong; Ima Nirwana, Soelaiman; Muhammad, Norliza; Fairus, Ahmad; Ng, Pei Yuen; Jamil, Nor Aini; Abd Aziz, Noorazah; Mohamed, Norazlina
Abstract: Background: Body mass index (BMI) is a widely used surrogate tool to screen for obesity/adiposity, but it cannot differentiate between lean and fat mass. Thus, alternative tools to detect excess adiposity should be identified. Aim: This study aimed to compare the performance of BMI, waist circumference (WC) and waist-to-height ratio (WtHR) in predicting Malaysians with excess body fat defined by dual-energy X-ray absorptiometry (DXA). Subjects and methods: A total of 399 men and women aged ≥40 years were recruited from Klang Valley, Malaysia. The body composition of the subjects, including body fat percentage, was measured by DXA. The weight, height, WC and WHtR of the subjects were also determined. Results: BMI [sensitivity = 55.7%, specificity = 86.1%, area under curve (AUC) = 0.709] and WC (sensitivity = 62.7%, specificity = 90.3%, AUC = 0.765) performed moderately in predicting excess adiposity. Their performance and sensitivity improved with lower cut-off values. The performance of WHtR (sensitivity = 96.6%, specificity = 36.1, AUC = 0.664) was optimal at the standard cut-off value and no modification was required. Conclusion: The performance of WC in identifying excess adiposity was greater than BMI and WHtR based on AUC values. Modification of cut-off values for BMI and WC could improve their performance and should be considered by healthcare providers in screening individuals with excess adiposity.